Characteristic Infrasound Events Associated with Sea-Ice Discharges in the L√ºtzow-Holm Bay of Antarctica : April 2016 - Kanao, Masaki (2019)
Infrasound waves detected in Antarctica contain information on the physical interaction among the surface environment at the margin of the continent and surrounding ocean. Time-space variation of source location for infrasound excitation during mid-April 2016 was investigated by using a combination of two arrays deployed along the coast of the L√ºtzow-Holm Bay (LHB), East Antarctica. The infrasound array observations detected temporal variations in distance from the sources and propagation direction. A few tens of infrasound events were identified during 10¬†days of the period, and many of them located in the northward direction from the array stations were inside the LHB and offshore in the Southern Indian Ocean. Many of the events had predominant frequency content of few Hz, which were higher than microbaroms generated from the ocean. By comparing with MODIS satellite image at the same period, these sources were considered to be the ice-related phenomenon associated with the discharge of fast sea ice from the LHB.